Pengaruh Pembelajaran STEM (Science,Technology, Engineering and Mathematics) dengan Media Interaktif Mobile Learning Nearpod Terhadap Keterampilan Kolaboratif dan Hasil Belajar Biologi Siswa SMA di Sekolah Kawasan Agroekosistem - Septya Lugita Tri Rahayu (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study was motivated by the low level of students' collaborative skills, as observed during initial observations at the school, as well as the need for learning innovations relevant to the demands of the 21st century, particularly in an agroecosystem-based school environment. Conventional learning models were considered suboptimal in facilitating student interaction and learning outcomes in complex biology material. This study aimed to examine the effect of the STEM (Science, Technology, Engineering, and Mathematics) learning model, supported by the interactive mobile learning platform (Nearpod), on the collaborative skills and biology learning outcomes of 10th-grade students in an agroecosystem-based school. This study employed a quantitative approach using a quasi-experimental design with a Non-Equivalent Control Group. The study population consisted of all 10th-grade students at MAN 1 Jember for the 2025/2026 academic year. The sample comprised two classes (an experimental class and a control class), selected via random sampling. Data were collected using observation sheets for collaborative skills, affective learning outcomes, and psychomotor learning outcomes, then analyzed using the Independent Sample T-Test. Cognitive learning outcome tests (pre-test and post-Test) were analyzed using the ANCOVA test. The results of the study showed a significance value of 0.000 (<0,05) for all variables: collaborative skills, as well as cognitive, affective, and psychomotor learning outcomes. This demonstrated that the implementation of the Nearpod-assisted STEM model had a significant effect on improving students' collaborative skills and biology learning outcomes. This model proved effective in creating interactive, collaborative, and flexible learning in schools based on agroecosystem environments. Keywords: agroecosystem, collaborative learning, learning outcomes, mobile learning, STEM
:: Finalisasi file repositori 21 Juli 2026_Kurnadi
Keywords: Agroekosistem; STEM Education; Mobile Learning